2014
DOI: 10.1038/onc.2014.153
|View full text |Cite
|
Sign up to set email alerts
|

PRKACA mediates resistance to HER2-targeted therapy in breast cancer cells and restores anti-apoptotic signaling

Abstract: Targeting HER2 with antibodies or small molecule inhibitors in HER2-positive breast cancer leads to improved survival, but resistance is a common clinical problem. To uncover novel mechanisms of resistance to anti-HER2 therapy in breast cancer, we performed a kinase open reading frame (ORF) screen to identify genes that rescue HER2-amplified breast cancer cells from HER2 inhibition or suppression. In addition to multiple members of the MAPK and PI3K signaling pathways, we discovered that expression of the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 45 publications
5
88
0
Order By: Relevance
“…Bcl-XL) in combination with anti-HER2 therapy may prevent the emergence of resistant disease. This study provides a rationale for further investigation of combined anti-HER2 and anti-Bcl-XL/ Bcl-2 therapy in HER2+ breast cancers [38].…”
Section: Multiple Kinases Activationmentioning
confidence: 97%
See 1 more Smart Citation
“…Bcl-XL) in combination with anti-HER2 therapy may prevent the emergence of resistant disease. This study provides a rationale for further investigation of combined anti-HER2 and anti-Bcl-XL/ Bcl-2 therapy in HER2+ breast cancers [38].…”
Section: Multiple Kinases Activationmentioning
confidence: 97%
“…Moody and colleagues [38] demonstrated that the overexpression of the survival kinases PRKACA and PIM1 leads to resistance to anti-HER2 therapy with trastuzumab and lapatinib. They identified the survival mechanism by which both PRKACA and PIM1 promote resistance to anti-HER2 therapy.…”
Section: Multiple Kinases Activationmentioning
confidence: 98%
“…In addition, circulating PRKACA has been detected in the sera of patients affected by carcinomas of the colon, kidney, rectum, prostate, lung, adrenal gland, as well as those with lymphomas (30)(31)(32). Moreover, patients resistant to trastuzumab show increased PRKACA expression (33). In this context, PRKACA might be a good biomarker and predictor of poor clinical outcome (33).…”
Section: Del Gobbo a Et Almentioning
confidence: 97%
“…And treatment-induced toxicity, which can impair quality of life can't be ignored (Barroso-Sousa et al, 2013). Many studies are under carrying out, for the relatively newer one, Moody et al (2014) observed elevated PRKACA expression in trastuzumab-resistant breast cancer, inactivating the pro-apoptotic protein BAD, the BCl-2-associated death promoter, but not by the usual MAPK or PI3K way. And they declare combined targeting of HER2 and the BCL-XL/BCL-2 anti-apoptotic pathway may increase responses to anti-HER2 therapy in breast cancer (Moody et al, 2014).…”
Section: Treatment Of Breast Cancermentioning
confidence: 99%
“…Many studies are under carrying out, for the relatively newer one, Moody et al (2014) observed elevated PRKACA expression in trastuzumab-resistant breast cancer, inactivating the pro-apoptotic protein BAD, the BCl-2-associated death promoter, but not by the usual MAPK or PI3K way. And they declare combined targeting of HER2 and the BCL-XL/BCL-2 anti-apoptotic pathway may increase responses to anti-HER2 therapy in breast cancer (Moody et al, 2014). From studies of Liqun Chen et al (Chen and Bourguignon, 2014), we further conjecture the possible mechanism may be upregulation of survival protein (Bcl-2/IAP), which is induced by c-Jun (member of the mitogen activated protein kinase family) signaling.…”
Section: Treatment Of Breast Cancermentioning
confidence: 99%